PENGARUH MODEL PEMBELAJARAN AIR (AUDITORY INTELLECTUALLY REPETITION) BERBANTUAN VIMABEL TERHADAP BERPIKIR KRITIS MATEMATIKA - Anisa Rahma Wati; Zulmi Rostika Rini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Critical thinking is a crucial higher-order thinking skill that should be fostered from the early years of elementary education, particularly in mathematics learning. Nevertheless, existing instructional practices in elementary schools often rely on teacher-centered approaches and provide limited integration of digital learning media, resulting in underdeveloped critical thinking skills among students. This study offers by integrating the AIR (Auditory, Intellectually, Repetition) learning model with VIMABEL (Video Matematika Belajar), a video-based instructional medium specifically designed for lower-grade elementary students. The study aims to examine both the differences and the effect of this integrated approach on students’ mathematical critical thinking skills. A quantitative quasi-experimental method with a nonequivalent control group design was employed. Participants were third-grade students at SD Negeri Suruh 01, assigned to an experimental group using the AIR model assisted by VIMABEL and a control group using the AIR model without media support. Data were collected through critical thinking tests, observations, and questionnaires, and analyzed using prerequisite tests, independent sample t-tests. The results demonstrate a significant difference in critical thinking skills between the two groups, as well as a significant positive effect of the AIR learning model assisted by VIMABEL on students’ mathematical critical thinking abilities. These findings highlight the potential of integrating structured learning models with contextually designed video media as an innovative and effective strategy to enhance critical thinking skills in elementary mathematics education.